Implementation science for dietitians: The 'what, why and how' using multiple case studies. - Young, Adrienne M.; Hickman, Ingrid; Campbell, Katrina; Wilkinson, Shelley A. (Nutrition & Dietetics, 2021)
Aim: Implementation science theories, models and frameworks help to address evidence‐practice gaps, which have increasing importance for dietetic practice. This paper aims to provide dietitians with insight into how implementation science can be applied to practice, using multiple 'real‐life' case studies. Methods: Three case studies were purposively selected across areas of dietetics practice to demonstrate application of commonly‐used implementation theories, models and frameworks. Reflections from the authors were provided in response to a structured set of questions outlining how the theoretical approach was selected and used, and considerations for future application. Within and cross‐case analysis was undertaken. Results: Dietitians used diverse implementation theories, models and frameworks to identify barriers and enablers, to plan for implementation, and to guide the selection of implementation strategies. Implementation theory was used to evaluate the implementation process in one case study. Cross‐case analysis identified that mentoring by those with implementation expertise, multidisciplinary implementation teams, and leadership and investment in research and translation at an organisational and departmental level as key enablers. Conclusions: This paper offers dietitians insight into how implementation science can be applied to improve the uptake of evidence‐based practices within nutrition and dietetics, and suggests that there needs to be investment in implementation science as a foundation science within nutrition and dietetics, including education, training and mentoring for dietitians.